Influence of various geometrical shapes on mixed convection through an open-cell aluminium foam filled with nanofluid - Mahdi R.A.; Mohammed H.A.; Munisamy K.M.; Saeid N.H. (2023)
Mixed convection heat transfer and fluid flow through an open-cell aluminium foam around various heat source shapes with constant heat flux inside rectangular horizontal channel, filled with nanofluid is numerically investigated. An open-cell aluminium foam is made of alloy 6101-T6 with porosity 93% and pore densities (10,40) PPI. Nanofluid with three different types of nanoparticles, aluminium oxide (Al2O3), copper oxide (CuO) and silicon dioxide (SiO2) with volume fraction of 4% and nanoparticle diameter of (25 nm) dispersed in water are used. Four models of cylindrical shapes are employed as test sections: (model 1) aluminium foam is around a rectangular cylinder (? = 90°),(model 2) the aluminium foam is around a trapezoidal cylinder shape (? = 82.875°), (model 3) aluminium foam is around a trapezoidal cylinder shape (? = 75.964°) and (model 4) the aluminium foam is around the triangular cylinder shape (? = 63.435°). In all models, the heat flux is 300 W/m2 and, aluminium foam length of (5 cm) is used with Reynolds number range of (200-600). The governing equations continuity, momentum and energy are solved by using the Finite-volume method (FVM). The effects of aluminium foam, nanofluid properties and Reynolds number on the Nusselt number and friction factor values, with four models in a rectangular horizontal channel are investigated. The results have shown that higher average Nusselt number is obtained with the use of nanofluid (water+SiO2) and 40PPI aluminium foam pore density at higher Reynolds number with model (4). Low friction factor is obtained with the use of nanofluid (water+SiO2) and 10PPI aluminium foam pore density at higher Reynolds number with model (4). Average Nusselt number increases and friction factor decreases when Reynolds number value increases with all models. Copyright © 2014 American Scientific Publishers.